1991
DOI: 10.1007/bf01313717
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism of microplankton communities in the northern Strait of Georgia, British Columbia

Abstract: Abstract. The northern Strait of Georgia, British Columbia, Canada, was sampled five times between March and September 1986, employing a grid of stations spanning the strait. The spring diatom bloom was not observed and may have been suppressed by a combination of wind exposure and grazing by microzooplankton, notably non-loricate oligotrichs and the dinoflagellate Gyrodinium spirale. Macrozooplankton were not studied. By June, the ecosystem was dominated by flagellates, and ciliate biomass was three times gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 76 publications
6
19
0
Order By: Relevance
“…Further north in the metals such as copper (Iizuka & Irie 1969). Perhaps Strait of Georgia, where stratification due to salinity is there was also a retention mechanism at work similar less s~gnificant, the spring bloom may even be supto that found by Anderson & Stolzenbach (1985) who pressed by winds (Haigh & Taylor 1991). Plankton reported that H. triquetra migrated downwards during succession on the outer coast typically lags that in the the ebb tide in an embayment and was not flushed out Strait by 1 mo.…”
Section: Spring Bloommentioning
confidence: 97%
See 1 more Smart Citation
“…Further north in the metals such as copper (Iizuka & Irie 1969). Perhaps Strait of Georgia, where stratification due to salinity is there was also a retention mechanism at work similar less s~gnificant, the spring bloom may even be supto that found by Anderson & Stolzenbach (1985) who pressed by winds (Haigh & Taylor 1991). Plankton reported that H. triquetra migrated downwards during succession on the outer coast typically lags that in the the ebb tide in an embayment and was not flushed out Strait by 1 mo.…”
Section: Spring Bloommentioning
confidence: 97%
“…Consequently, a plankton study was needed for industry to choose optimal sites: those which balance high productivity and potentially harmful effects due to noxious plankton. This was not done prior to the establishment of farms and there was a loss to the local industry of Can$2.5 million (Taylor et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that: (1) oligotrichs similar to those presented in Table 4 are almost always present at average concentrations of 1 to 10 cells ml-' (Fenchel 1987, Lynn & Montagnes 1991, therefore ciliates must be surviving in situ; (2) estimates of prey biomass (2 to 20 pm in diameter) In coastal waters, where ciliates have been examined, often range between 5 and 50 ng C ml-' (e.g. Smetacek 1981, for Kiel Bight, Andersen & Smensen 1986, for Danish waters; , for the NW Mediterranean Sea; Haigh & Taylor 1991, Halgh et al 1992, for NE Pacific waters); (3) oligotrich maxlmum growth rates occur at concentrations > l 0 0 ng C m l l (Table 4), which are above typical prey biomass levels: (4) ciliate threshold concentrations range around 10 to 100 ng C ml-' (Table 4 ) , which are also near or above typical prey biomass levels; and (5) cillates die over a period of hours to days when food levels are depleted below threshold concentrations. These data suggest that since cillates are present In the plankton, they must encounter prey concentrations of > l 0 ng C ml-' to survive.…”
Section: An Ecological Implication Of the Numerical Responsesmentioning
confidence: 99%
“…1). The most likely source of error introduced months (Haigh & Taylor 1991). This observation sugby using t h~s sampling platform was the inclusion of gests that differences in species compositions of phytobenthic species with pelagic ones, particularly during plankton across fronts can be caused by variations in storms.…”
Section: Introductionmentioning
confidence: 99%